Indonesian EFL Teachers' Perceptions on Formative Assessment in Writing - Wijaya, Kristian Florensio (JET (Journal of English Teaching), 2022)
Abstract Traditionally, the previous writing learning enterprise strictly focused its concern on gaining the fixed results from EFL educators in the form of scores or judgments. However, nowadays writing learning venture gradually abandons this old method to be replaced by formative assessment approach. It is strongly believed by worldwide researchers that the suitable implementation of formative assessment can enable learners to yield better writing qualities, gain more satisfying writing achievements, and foster their writing learning motivation. This present small-scale study was planned to further investigate Indonesian EFL teachers’ perceptions on the use of formative assessment in EFL writing. The data gathering processes relied on 5 open-ended written narrative inquiry questions in order to provide more rejuvenating insights for ELT experts and practitioners. These inquiries were distributed to 2 experienced Indonesian EFL teachers holding English Education Master Degree. 2 major specific themes were scientifically obtained namely: (1) Formative assessment can intensively guide learners to improve the quality of their writing and (2) Formative assessment can promote more holistic writing learning venture for all learners. Suggestively, these 2 themes aimed to suggest worldwide ELT parties to exhaustively preparing more authentic formative writing assessment activities for the betterment of future writing learning dynamics. Keywords: Formative assessment, EFL teachers, writing